NGHIÊN CỨU ẢNH HƯỞNG CỦA PHỐI TỬ ĐẾN KHẢ NĂNG THĂNG HOA CỦA CÁC CACBOXYLAT ĐẤT HIẾM - Nguyệt, Triệu Thị; Hiền Lan, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
26 carboxylate complexes (acetate (Acet), isobutyrate (Isb), isopentanoate (Isp), 2-metylbutyrate (2-Meb), pivalate (Piv)) of rare earths (Nd, Sm, Gd, Ho, Er, Yb) and 20 mixed complexes of these carboxylates with o-phenantroline Ln(Cab)3.Phen (Cab: Acet, Isb, Isp, 2-Meb, Piv; Phen: o-phenantroline) have been synthesized and their sublimation ability has been studied. The results of the study have indicated that pivalates can evaporate the best. The mixed complexes sublimate better than their corresponding carboxylates. The more bulky the hydrocarbon root is, the more limited the polymerization ability of carboxylate is, therefore the complexes are higher sublimability.